Correlation of Fasting Blood Glucose Levels and HbA1c with Body Mass Index in Type 2 Diabetes Mellitus Patients - Anik Handayati; Lully Hanni Endarini; Yuni Eka Cahyana (Health Notions, 2022)
Excess body mass index is at greater risk of developing diabetes mellitus than other diseases. Monitoring blood glucose includes through examination of fasting blood glucose levels and HbA1c. This study aims to find out the relationship of fasting blood glucose levels and HbA1c with Body Mass Index in type 2 diabetes mellitus patients. This study was an observational analytical study with a cross sectional design. The research was conducted at Prima Surabaya Main Clinic in January to June 2021. The sample was a type 2 diabetes mellitus patient who conducted fasting blood glucose examination, HbA1c and Body Mass Index measurement at Prima Surabaya Main Clinic as many as 40 people, were taken purposive sampling. The results of this study found that the average fasting blood glucose level of patients with type 2 diabetes mellitus was 172.6 mg / dL and HbA1c was 7.76%. The average Body Mass Index was 24.97. Pearson correlation test results obtained significant Body Mass Index with fasting blood glucose levels p = 0.150 and HbA1c with Body Mass Index p = 0.295, which means there is no relationship between fasting blood glucose levels and HbA1c with body mass index in type 2 diabetes mellitus patients.  Keywords: fasting blood glucose; HbA1c; Body Mass Index; auto analyzer